ADMINISTRATIVE LAW AND THE OVERSIGHT OF STATE FINANCES IN THE DIGITAL GOVERNMENT ERA - Alila Zahira Kusuma; Cholidah Utama (Multidisciplinary Research Studies in Social Sciences, 2025)
The rapid digital transformation of public administration has reshaped how governments manage and supervise state finances, making the intersection between administrative law and digital governance increasingly urgent. This study aims to analyze how administrative law supports the effectiveness of financial oversight in the digital era, emphasizing regulatory reform and the adoption of technologies such as e-budgeting and artificial intelligence (AI). Employing a descriptive qualitative method with a library research and document analysis approach, the research examines legal and institutional frameworks from seven countries Indonesia, Italy, Ukraine, Ireland, India, Brazil, and Poland using secondary data from 2020–2025. The findings reveal that countries with adaptive administrative legal structures and high AI adoption rates (India 65%, Ireland 60%) demonstrate stronger fiscal transparency, as reflected in the Digital Budget Transparency Index (India 88, Italy 85). The study concludes that digital transformation must be complemented by robust legal reform to ensure accountability and legitimacy in fiscal governance. The research contributes to administrative law scholarship by highlighting the synergy between law and technology in enhancing public sector transparency. Future studies should employ triangulated or field-based methods to assess the practical effectiveness of AI-driven oversight within national audit institutions.Keywords: administrative law, digital governance, fiscal transparency, artificial intelligence, public finance oversight.